Radiological signs associated with pulmonary multi-drug resistant tuberculosis: an analysis of published evidences - Wáng, Yì Xiáng J.; Chung, Myung Jin; Skrahin, Aliaksandr; Rosenthal, Alex; Gabrielian, Andrei; Tartakovsky, Michael (Quantitative Imaging in Medicine and Surgery; Vol 8, No 2 (March 28, 2018): Quantitative Imaging in Medicine and Surgery, 2018)
Background: Despite that confirmative diagnosis of pulmonary drug-sensitive tuberculosis (DS-TB) and multidrug resistant tuberculosis (MDR-TB) is determined by microbiological testing, early suspicions of MDR-TB by chest imaging are highly desirable in order to guide diagnostic process. We aim to perform an analysis of currently available literatures on radiological signs associated with pulmonary MDR-TB. Methods: A literature search was performed using PubMed on January 29, 2018. The search words combination was “((extensive* drug resistant tuberculosis) OR (multidrug-resistant tuberculosis)) AND (CT or radiograph or imaging or X-ray or computed tomography)”. We analyzed English language articles reported sufficient information of radiological signs of DS-TB vs. MDR-TB. Results: Seventeen articles were found to be sufficiently relevant and included for analysis. The reported pulmonary MDR-TB cases were grouped into four categories: (I) previously treated (or ‘secondary’, or ‘acquired’) MDR-TB in HIV negative (−) adults; (II) new (or ‘primary’) MDR-TB in HIV(−) adults; (III) MDR-TB in HIV positive (+) adults; and (IV) MDR-TB in child patients. The common radiological findings of pulmonary MDR-TB included centrilobular small nodules, branching linear and nodular opacities (tree-in-bud sign), patchy or lobular areas of consolidation, cavitation, and bronchiectasis. While overall MDR-TB cases tended to have more extensive disease, more likely to be bilateral, to have pleural involvement, to have bronchiectasis, and to have lung volume loss; these signs alone were not sufficient for differential diagnosis of MDR-TB. Current literatures suggest that the radiological sign which may offer good specificity for pulmonary MDR-TB diagnosis, though maybe at the cost of low sensitivity, would be thick-walled multiple cavities, particularly if the cavity number is ≥3. For adult HIV(−) patients, new MDR-TB appear to show similar prevalence of cavity lesion, which was estimated to be around 70%, compared with previously treated MDR-TB. Conclusions: Thick-walled multiple cavity lesions present the most promising radiological sign for MDR-TB diagnosis. For future studies cavity lesion characteristics should be quantified in details.